Effectiveness Of Multimedia Courseware Based Instruction on Senior School Students' Retention in Linear Equation Word Problems - Khadijat Saka Ameen; Ridwan Enuwa Mohammed; Bala Ayuba (MO.RI Publishing, 2023)
The use of Multimedia courseware during teaching and learning is becoming progressively popular to overcome the abstract concepts within the subject and underachievement of the students. The study investigated the effects of multimedia courseware-based instruction on senior school students' achievement and retention in linear equation word problems in Mathematics. In Gombe State Nigeria, 120 students (69 males and 51 females) were selected from three co-educational senior schools allocated either into experimental group or a control group. The study adopted a quasi-experimental research design. It used a pre-test, post-test, non-randomized, non-equivalent control group involving a  factorial matrix. Mathematics Achievement Test on Linear Equations Word Problems in Mathematics (MAT) was used for collecting data and Multimedia Courseware on Linear Equations Word Problems in Mathematics (MCLEWPM) was used as a treatment instrument. The validated MAT was tested for reliability using Pearson Product Moment Correlation (PPMC), which yielded 0.78 at 0.05 alpha level of significance, indicating that the MAT is reliable with good construct validity. MAT was administered on students in experimental and control groups and data obtained were analyzed using T-test and Analysis of Covariance (ANCOVA) to test the hypotheses. The results of the study indicated that students exposed to multimedia courseware-based instruction achieved and retained linear equation word problems than their counterparts who were exposed to conventional teaching method. There was significant difference between the mean retention scores of male and female students exposed to multimedia courseware-based instructions which the result is in favor of female students. High, medium and low achievers' students exposed to multimedia courseware-based instructions retained the concept of linear equations involving word problems and high scorer retained better. Based on the above findings it was recommended that multimedia courseware-based instruction should be used in teaching and learning of Mathematics as it was found capable of improving students' retention in linear equation word problems in Mathematics.